2012
DOI: 10.1590/s0074-02762012000200014
|View full text |Cite
|
Sign up to set email alerts
|

Kinetoplastid membrane protein-11 exacerbates infection with Leishmania amazonensis in murine macrophages

Abstract: In Leishmania amazonensis, kinetoplastid membrane protein-11 (KMP-11) expression increases during metacyclogenesis and is higher in amastigotes than in promastigotes, suggesting a role for this protein in the infection of the mammalian host. We show that the addition of KMP-11 exacerbates L. amazonensis infection in peritoneal macrophages from BALB/c mice by increasing interleukin (IL)-10 secretion and arginase activity while reducing nitric oxide (NO) production. The doses of KMP-11, the IL-10 levels and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…LPS in recombinant protein KMP-11 was completely removed by passing through polymyxin B-agarose column (Sigma, USA) according to the manufacturer's instructions and confirmed by LAL test. The recombinant KMP-11 protein was then stored at −80°C for further use [17]. …”
Section: Methodsmentioning
confidence: 99%
“…LPS in recombinant protein KMP-11 was completely removed by passing through polymyxin B-agarose column (Sigma, USA) according to the manufacturer's instructions and confirmed by LAL test. The recombinant KMP-11 protein was then stored at −80°C for further use [17]. …”
Section: Methodsmentioning
confidence: 99%
“…In vitro experiments have demonstrated that during Leishmania infection, there is increased production of arginase-I, transforming growth factor β (TGF-β) and HO-1 by infected macrophages, which has been associated with augmented intracellular parasite proliferation78910. Moreover, the role of these three important mediators in Leishmania infection has been further established in experiments using macrophages from mice genetically lacking HO-111, and pharmacological inhibition of arginase-I7 or antibody-mediated blockage of TGF-β12 in infected human macrophages.…”
mentioning
confidence: 99%
“…Another Leishmania pathogenicity factor, the kinetoplastid membrane protein-11 (KMP-11), whose expression is increased during metacyclogenesis and in L. amazonensis amastigote stage, was shown to exacerbate BALB/c mice peritoneal macrophages infection by increasing IL-10 secretion [65,66]. KMP-11 was also shown to increase the macrophage arginase activity while reducing the nitric oxide production, thus promoting parasite survival [65].…”
Section: -By the Amastigotementioning
confidence: 99%
“…KMP-11 was also shown to increase the macrophage arginase activity while reducing the nitric oxide production, thus promoting parasite survival [65]. KMP-11 is currently regarded as a potential vaccine target [67].…”
Section: -By the Amastigotementioning
confidence: 99%